High incidence of drug‐resistant Mycobacterium tuberculosis in Hainan Island, China. Issue 9 (23rd July 2019) - Lin, Mingguan; Zhong, Yeteng; Chen, Zhuolin; Lin, Chong; Pei, Hua; Shu, Wei; Pang, Yu
Abstract: Objectives: To assess the proportion of drug‐resistant tuberculosis (TB) cases and to identify independent risk factors associated with drug‐resistant TB in Hainan. Methods: Descriptive analysis of demographic and clinical data of culture‐positive TB patients to assess the trends in drug‐resistant TB at the Provincial Clinical Center on Tuberculosis of Hainan between 2014 and 2017. Results: 994 patients were recruited into the study. Overall, the proportion of patients resistant to at least one TB drug tested was 36.1% (359/994). The most frequent resistance was to isoniazid (INH, 29.8%), followed by rifampin (RIF, 29.3%), streptomycin (19.3%), ofloxacin (OFX, 17.4%), ethambutol (9.5%) and kanamycin (KAN, 3.2%). Of 291 RIF‐resistant isolates, 228 (78.4%) were also resistant to INH, while the remaining 63 (21.6%) were susceptible to INH. Among those with multidrug‐resistant tuberculosis (MDR‐TB), 41.2% had additional resistance to OFX and 3.9% to KAN. 8.8% of MDR‐TB patients were affected by extensively drug‐resistant (XDR‐TB). Females were more likely to infected with MDR‐TB than males, and young people (<20 years old) were more likely to have MDR‐TB; patients exhibited decreasing MDR‐TB risk with increasing age. Conclusions: Our data provide the first primary understanding of the drug‐resistant TB epidemic in Hainan. The high incidence of drug resistance, especially RIF and FQ resistance, highlight the importance of interventions for preventing epidemics of drug‐resistant TB. Younger age is an independent predictor of MDR‐TB, reflecting the potential transmission in this population. Abstract : Objectifs: Evaluer la proportion de cas de tuberculose (TB) résistante aux médicaments et identifier les facteurs de risque indépendants associés à la TB résistante à Hainan. Méthodes: Analyse descriptive des données démographiques et cliniques de patients TB à culture positive pour évaluer les tendances de la TB résistante au Centre Clinique Provincial de la TB de Hainan entre 2014 et 2017. Résultats: 994 patients ont été recrutés dans l'étude. Au total, la proportion de patients résistant à au moins un antituberculeux testé était de 36, 1% (359/994). La résistance la plus fréquente était à l'isoniazide (INH, 29, 8%), suivi par la rifampine (RIF, 29, 3%), la streptomycine (19, 3%), l'ofloxacine (OFX, 17, 4%), l'éthambutol (9, 5%) et la kanamycine (KAN, 3, 2%). Sur les 291 isolats résistants au RIF, 228 (78, 4%) étaient également résistants à l'INH, tandis que les 63 restants (21, 6%) étaient sensibles à l'INH. Parmi ceux avec la multirésistance (TB‐MDR), 41, 2% présentaient une résistance supplémentaire à l'OFX et 3, 9% à la KAN. 8, 8% des patients atteints de TB‐MDR étaient atteints d'une TB ultrarésistante (TB‐XDR). Les femmes étaient plus susceptibles d'être infectées par la TB‐MDR que les hommes et les jeunes (<20 ans) étaient plus susceptibles d'être atteints de TB‐MDR; les patients présentaient un risque décroissant de TB‐MDR avec l'âge. Conclusions: Nos données fournissent la première compréhension importante de l'épidémie de TB résistante à Hainan. L'incidence élevée de la résistance aux médicaments, en particulier des résistances RIF et FQ, souligne l'importance des interventions pour prévenir les épidémies de TB résistante. L'âge plus jeune est un facteur indépendant de prédiction de la TB‐MDR, reflétant le potentiel de transmission dans cette population.